Conflict, Interdependence, and Justice The Intellectual Legacy of Morton Deutsch - Coleman, Peter T.; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Morton Deutsch is considered the founder of modern conflict resolution theory and practice. He has written and researched areas which pioneered current efforts in conflict resolution and diplomacy. This volume showcases six of Deutsch$1 (Bs more notable and influential papers, and include complementary chapters written by other significant contributors working in these areas who can situate the original papers in the context of the existing state of scholarship.s
Introduction: Morton Deutsch and the Science of Peace -- A Career in Social Psychology -- Cooperation and Competition -- Intellectual Legacy: Cooperation and Competition -- Justice and Conflict -- Injustice and the Private Sphere -- Awakening a Sense of Injustice -- Awakening in a New Century -- A Framework for Thinking about Oppression -- Dismantling Oppression and Ushering in Social Change: A System Justification Perspective -- Interdependence and Psychological Orientation -- Coherence, Fit And Flow: A Framework For Envisioning The Fundamental Dynamics Of Social Relations -- Conclusion: Reflections on the State of the Field of Peace Psychology.
Keywords: Philosophy (General).; Consciousness; Psychology; Personality and Social Psychology